A photothermally triggered one-component shape memory polymer material prepared by cross-linking porphyrin-based amphiphilic copolymer self-assemblies. Issue 30 (21st July 2022) - Song, Yufang; Chen, Yiming; Qian, Wangqiu; Shi, Dongjian; Dong, Weifu; Wang, Yang; Ma, Piming; Zhang, Hongji
Abstract : We provided a new strategy to design a photothermally triggered one-component shape memory polymer. The porphyrin moiety was covalently bonded into the amphiphilic copolymer chain, which enhanced its photothermal conversion ability through self-assembly. Abstract : Photothermally triggered shape memory polymer materials are usually prepared by dispersing photothermally responsive fillers or compounds into shape memory polymer matrixes through physical blending, while the migration and non-biodegradability of the fillers limit their potential applications ( e.g., in the biomedical field). Here, we synthesized a new type of porphyrin-based amphiphilic random copolymer bearing a reactive moiety of carbonyl group by co-polymerizing methyl methacrylate (MMA), butyl acrylate (BA), diacetone acrylamide (DAAM), acrylic acid (AA) and double-bonded vinyl porphyrin monomers, followed by induced self-assembly in aqueous solution to give rise to amphiphilic random copolymer nanoparticles. The nanoparticles were further crosslinked by means of adipic dihydrazide (ADH) to fabricate the photothermally triggered one-component shape memory polymer material. Compared with the most-studied multi-phase/multi-component shape memory polymer materials, the porphyrin moiety, playing the role of a photo-to-heat converter, covalently bonded into the polymer structure would certainly make it more homogeneous and more stable in principle.